계통연계형 인버터의 동기 좌표계를 이용한 단독운전 검출 알고리즘 - 송용규 (The Graduate School, Ajou University, 2015)
In the grid-connected system, anti-islanding method has been an important technical topic. Therefore, various anti-islanding methods for detecting and preventing islanding phenomenon have been proposed. Among them, an AFD (Active Frequency Drift) technique is commonly used as anti-islanding detection method. However, it has the disadvantage that the current THD and detection time are increased according to the gain of the AFD algorithm and it reduces the power quality. This paper proposed a novel antiislanding method to complement the shortcomings of AFD algorithms. By using proposed method, change of the gain does not affect the power quality and detection time is faster than general AFD method. In addition, it is easy to implement algorithm because of the simple structure of the controller. The effectiveness of the proposed method was demonstrated by the simulation and experiment results.
학위논문(석사)--아주대학교 일반대학원 :전자공학과,2015. 2
Keywords: 계통연계형